31.1k views
5 votes
Y=x-1 2x-3y=-1
y=6x-11 -2x-3y=7
y=-5x-17 -3x-3y=3
y=5x-7 -3x-2y=-12

1 Answer

6 votes

Answer:

(4,3)

Explanation:

y=x-1 2x-3y=-1

y=6x-11 -2x-3y=7

y=-5x-17 -3x-3y=3

y=5x-7 -3x-2y=-12

To solve a system of 2 variables, only 2 equations are required. Choose the first two equations containing the variables in the system.

y = x − 1 2 x − 3 y = − 1

Subtract x from both sides of the equation.

y − x = − 1 2 x − 3 y = − 1

Reorder the polynomial.

− x + y = − 1 2 x − 3 y = − 1

Multiply each equation by the value that makes the coefficients of x opposite.

( 2 ) ⋅ ( − x + y ) = ( 2 ) ( − 1 ) 2 x − 3 y = − 1

Simplify.

− 2 x + 2 y = − 2 2 x − 3 y = − 1

Add the two equations together to eliminate x from the system.

− 2 x + 2 y = − 2 + 2 x − 3 y = − 1 − y = − 3

Multiply each term in − y = − 3 by − 1

y = 3

Substitute the value found for y into one of the original equations, then solve for x .

x = 4

The solution to the independent system of equations can be represented as a point.

( 4 , 3 )

The result can be shown in multiple forms.

Point Form:

( 4 , 3 )

Equation Form:

x = 4 , y = 3

Hope This helps bro, good luck , and have a good day :)

User Gurbir
by
5.8k points